Preschool teachers’ perspectives on using English language to teach - Goh, Pauline Swee-Choo (Penerbit Universiti Kebangsaan Malaysia, 2019)
In the Malaysian National Preschool Standards-based Curriculum context, preschool teachers are being asked to use English as a medium of instruction for part of their teaching activities. However, there have been criticisms that low English language proficiencies among these teachers may have hindered their ability to provide meaningful educational experiences for the children in their care. Yet, little is understood about the language proficiency of these teachers in their own context. An explanatory mixed methods design has been used in the present study with data collected in two phases. In the quantitative phase, a survey is used to investigate 204 preschool teachers’ current levels of English proficiency, the levels they think necessary for using it effectively, and the gap between the two levels. The qualitative phase uses semi-structured interviews with 12 preschool teachers. The preschool teachers believe that high or advanced language proficiency would be needed for its effective use. However, in the interviews, they also consider empathy for the children, a passion for teaching, the ability to make the class fun and interesting as equally important. There is also a lot of ‘language switching’ between English, the Malay language and the mother tongue to meet the requirements of the day’s lesson. Although preschool teachers in general showed positive stances about the decision to use English for part of the instructional time, they also suggest that some form of benchmarks that address the kinds or levels of English language proficiency needed for its effective use would be useful.